Ecological correlates of activity-related behavior typologies among adolescents - Parker, Kate E. (BMC Public Health, 2019)
BACKGROUND: Adolescents engage in various combinations (typologies) of physical activity and sedentary behaviors, which impact their health and wellbeing in different ways. As such, there is a need to understand the factors that may inhibit or facilitate engagement in combinations of activity-related behaviors to help inform effective intervention strategies targeting those most in need. The aim of this study was to identify ecological correlates of adolescent physical activity and sedentary behavior typologies. METHODS: Cross-sectional study of 473 adolescents (15.0 ± 1.6 years, 41.4% boys) from 18 secondary schools in Melbourne, Australia. Intrapersonal, interpersonal and neighborhood-physical environmental factors were assessed via self-report surveys and Geographic Information Systems. Multinomial logistic regression models determined the relative risk ratio of membership of three homogenous activity-related behavior typologies based on the potential correlates. RESULTS: Higher levels of self-efficacy for physical activity, parental screen-time restriction rules, parental support for physical activity, sibling screen-time co-participation and perceptions of neighborhood pedestrian/traffic safety were associated with greater likelihood of adolescents being in the typology defined as highly active and low sedentary compared to the physically inactive, highly sedentary typology. Higher frequency of co-participation in screen-time with friends was associated with greater likelihood of adolescents being in the typology defined as moderately active, high screen-time compared to physically inactive, highly sedentary. CONCLUSIONS: A range of intrapersonal, interpersonal and environmental correlates appear to play a role in adolescent activity-related typology membership. The findings may inform public health interventions targeting unique adolescent subgroups most at risk of poor health outcomes based on their engagement in combinations of activity-related behaviors. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12889-019-7386-9) contains supplementary material, which is available to authorized users.